Superselective superior rectal artery embolization in the treatment of hemorrhoidal disease - Jiang, Tao; Fan, Lichao; Tang, Xuesong; Xu, Zhigang; Wu, Wenjiang (Frontiers in Medicine, 2025)
Hemorrhoids are a prevalent and benign anal disorder for which minimally invasive treatments are increasingly preferred. The UK National Institute for Health and Care Excellence clinical guideline (2010) recommends hemorrhoidal artery ligation as a treatment option for hemorrhoidal disease. Superior rectal artery embolization (SRAE) leverages this principle by using digital subtraction angiography to precisely identify and superselectively embolize the arteries supplying the hemorrhoidal region. This procedure has demonstrated favorable clinical outcomes. SRAE is minimally invasive, painless, preserves the anal sphincter and normal anal anatomy, and offers a quick recovery, establishing it as an effective minimally invasive surgical option. As a result, this technique has gained increasing clinical recognition and adoption. This article examines the efficacy and safety of superselective SRAE for hemorrhoidal disease.